1998
DOI: 10.1097/00000539-199809000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Effective Analgesia After Bilateral Tubal Ligation

Abstract: During bilateral tubal ligation with either spinal or epidural anesthesia, preemptive analgesia using IV ketorolac, IV metoclopramide, and infiltration of the incised skin and uterine tubes with 0.5% bupivacaine allowed 9 of 10 patients to recover with no pain, nausea, vomiting, or cramping and to maintain good analgesia for 7 days postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The localization of pain to the shoulder is due to the excitation of the diaphragm and phrenic nerve. The amount of gas used is directly proportional to the postoperative pain reported (Wittels et al, 1998). Aspiration of gas at the end of the case has been shown to decrease this pain.…”
Section: Laparoscopic Tubal Ligation Painmentioning
confidence: 99%
See 1 more Smart Citation
“…The localization of pain to the shoulder is due to the excitation of the diaphragm and phrenic nerve. The amount of gas used is directly proportional to the postoperative pain reported (Wittels et al, 1998). Aspiration of gas at the end of the case has been shown to decrease this pain.…”
Section: Laparoscopic Tubal Ligation Painmentioning
confidence: 99%
“…A patient undergoing a diagnostic laparoscopic procedure has much less reported pain than those with a laparoscopic tubal ligation or cholecystectomy (Davis & Miller, 1988). No one drug has been found effective in controlling all forms of pain associated with laparoscopic procedures (Wittels et al, 1998).…”
Section: Laparoscopic Tubal Ligation Painmentioning
confidence: 99%
“…Combining NSAIDs with a variety of other analgesia therapies such as local anesthetics, and opioids, as well as employing psychological support is referred to as balanced, or multimodal analgesia (Chung et al, 1997). A review of the Uterature revealed that taking a multimodal approach may be the most efficacious method in treating postoperative pain following laparoscopic tubal steriUzation (Alexander, 1997;Chung et al, 1997;Goldstein et al, 2000;Kelly et al, 1995;Wittels et al, 1998). Nonetheless, controversy exists in the literature concerning the optimal timing, route of administration, and combination of drugs, so further research is needed.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Drug modalities for this type of pain vary in regard to the use of opioids, NSAIDs, antispasmodics, and local anesthetics. As previously stated, many anesthesia researchers recommend employing a multimodal analgesia approach in attenuating postoperative laparoscopic sterilization pain (Alexander, 1997;Chung et al, 1997;Goldstein, 2000;Kelly et al, 1995;Wittels et al, 1998).…”
Section: Pain From Tubal Sterilizationmentioning
confidence: 99%
See 1 more Smart Citation